Pengembangan Sistem Informasi Database Alumni (Studi Kasus: SMAN 1 2x11 Enam Lingkung) - Sundari, Redha Ayu; Musril, Hari Antoni (Yayasan Petra Harapan Bangsa, 2020)
This research is motivated by the need for an alumni database information system at SMAN 1 2x11 Enam Lingkung. The school has produced many alumni each year. However, in the management of alumni data, no system can accommodate special data and information, thus allowing existing alumni data to be lost. To facilitate this, an alumni information system using code igniter is built. The research method used is the Research and Development (R & D) research method. The R&D research step used is 4D, namely: define, design, develop, and disseminate. The system development model uses a waterfall which consists of 5 stages, namely the definition of requirements, system and software design, implementation and unit testing, system integration and testing, and operation and maintenance. The results of the product validity test obtain a value of 0.77 which is stated valid, the results of the practicality of the product obtain a value of 91 which is stated very practical, and the results of the effectiveness of the product obtain a value of 0.89 which is stated very effective. Penelitian ini dilatarbelakangi oleh perlunya sistem informasi database alumni di SMAN 1 2x11 Enam Lingkung. Sekolah tersebut sudah menghasilkan banyak alumni tiap tahunnya. Namun, dalam pengelolaan data-data alumni belum ada sistem yang menjadi wadah data dan informasi khusus, sehingga memungkinkan data-data alumni yang ada bisa hilang. Untuk memudahkan hal tersebut, maka dibangun suatu sistem informasi alumni menggunakan code ignitier.Metode penelitian yang digunakan adalah metode penelitian Research and Development (R&D). Langkah penelitian R&D yang digunakan adalah 4D, yaitu:define, design, develop, dan disseminate.Model pengembangan sistem menggunakan waterfall yang terdiri dari 5 tahap, yaitu definisi persyaratan, perancangan sistem dan perangkat lunak, implementasi dan pengujian unit, integrasi dan pengujian sistem, serta operasi dan pemeliharaan. Hasil pengujian validitas produk memperoleh nilai 0,77 yang dinyatakan valid, hasil praktikalitas produk memperoleh nilai 91 yang dinyatakan sangat praktis, dan hasil efektivitas produk memperoleh nilai 0,89 yang dinyatakan sangat efektif.